Workplace violence toward resident doctors in public hospitals of Syria: prevalence, psychological impact, and prevention strategies: a cross-sectional study - Okbah Mohamad; Naseem AlKhoury; Mohammad-Nasan Abdul-Baki; Marah Alsalkini; Rafea Shaaban (Human Resources for Health, 2021)
Abstract Introduction Workplace violence (WPV) against healthcare workers is a common and daily problem in hospitals worldwide. Studies in different countries indicated that exposure to WPV potentially impacts the psychological status of healthcare workers. However, there is a paucity of studies approaching this issue in the Syrian healthcare system. Objectives This study had three objectives: (1) to estimate the prevalence of violence against resident doctors in Syria, (2) to examine the association between WPV and resident doctors’ psychological stress, sleep quality, depression, and general health and (3) to suggest approaches to tackle this problem from the resident doctors' perspectives. Methods A cross-sectional study was conducted in 8 out of 14 provinces, and covered 17 out of 56 accessible functioning hospitals in Syria. Data were collected using anonymous, self-administered questionnaires during February 2020. A total of 1226 resident doctors volunteered to participate in the study. Finally, 1127 valid questionnaires were used in the final data analysis. The overall response rate was 91.92%. Results A total of 955 participants (84.74%) reported exposure to WPV in the 12 months prior to the study. In specific, 84.74% exposed to verbal violence and 19.08% to physical violence. Patients’ associates were the predominant aggressors in both verbal and physical violence (n = 856; 89.63%, n = 178; 82.79%, respectively). Most resident doctors (87.31%) suggested enacting more legislation to protect doctors as the best solution to reduce WPV. Verbal and physical violence showed a significant positive correlation with each item of depression and stress, and a significant negative correlation with both subjective sleep quality and subjective health. Conclusion Workplace violence against resident doctors in Syria is highly common. Therefore, policymakers, hospital managers, and supervisors should work collaboratively in order to minimize WPV and ensure resident doctors’ safety and psychophysical stability.